Implementation and outcomes of a live continuing education program on pharmacogenomics. (June 2013) - Kuo, Grace M; Lee, Kelly C; Ma, Joseph D
Aim: This study evaluated the implementation and outcomes of a pharmacogenomics education program among pharmacists.Materials & methods: Continuing education lectures were presented at local, state and national pharmacy conferences.Results: Six hundred and seventy three pharmacist participants (mean ± standard deviation: 45 ± 14 years of age with 19 ± 13 years of practice experience) completed program evaluations. Participants' knowledge and overall ability to address pharmacogenomics testing significantly improved (p < 0.001). More than 50% rated self-efficacy for putting pharmacogenomics knowledge into clinical practice to be likely or very likely. Attitudes toward increasing the number of patients to educate, updating pharmacogenomics knowledge, and providing advice were 39, 76 and 64%, respectively. Participants rated program components to be useful or very useful, and the quality of the program format, program content and audience response system as good, very good or excellent.Conclusion: Through live continuing education presentations at pharmacy conferences, participants showed significant increases in knowledge and their overall ability to address pharmacogenomics testing with patients. Original submitted 30 January 2013; Revision submitted 10 April 2013